KESEIMBANGAN POLA-CITRA SIMPUL DAN KORIDOR TATA RUANG KOTA MULTILAYER LAMA-BARU PADA KAWASAN BERORIENTASI TRANSIT BLOK M JAKARTA - Retvianne, Ghina; Xaverius Budi Pangarso, Fransiscus (Jurnal Riset Arsitektur, 2024)
Abstract - Jakarta is the first city in Indonesia with the TOD (Transit Oriented Development) system. This research, with the theme of "millennial" city, sets out research on the development of TOD in DKI Jakarta with the main focus on the TOD area of ​​Blok M, DKI Jakarta. This study aims to understand the user's visual spatial experience based on the physical-spatial aspects of the KBT corridor in the form of the TOD (Transit Oriented Development) arrangement of the Blok M area and to understand the relationship between the old-new aspects of the Blok M Plaza and Blok M Square built areas to the TOD corridor. (Transit Oriented Development) Blok M. This research is descriptive qualitative, with an approach referring to the theory of The Concise Townscape, The Aesthetic Townscape, Street and Pattern, and The Principles of TOD as the basis of the literature that underlies this research. The literature that has been mentioned will become a parameter in collecting research data. The research method is based on the sequence of the Blok M Square area with the boundaries of the Blok M terminal building until the formation of the MRT Station. The conclusions obtained resulted in the concept of balance from the old-new area in the observation point period starting from the MRT Station Node, Martha Tiahahu Interchange Corridor, Bus Terminal Interchange Corridor, and Blok M Bus Terminal Node. This research is expected to be one of the references in research related to visual imagery urban space in other cities, especially in the context of KBT (Transit Oriented Areas). Keywords: Transit Oriented Development, pictorial graphic, Blok M, townscape